DUKUNGAN SOSIAL KELUARGA PADA PASIEN GANGGUAN ANSIETAS MENYELURUH DI INSTALASI RAWAT JALAN RUMAH SAKIT BAPTIS KEDIRI - Triyoga, Akde; Hermawan, Hermawan (Jurnal Penelitian STIKES Kediri, 2011)
backgorund : General Anxiety Disorder is an excessive fear and internalized about some event or activity within a few days at least - 6 months period. Family social support is a condition that is useful for individuals that obtained from another person who can be trusted, so that someone will know that there are others who pay attention, respect and love him. More specifically the existence of adequate social family support proved associated with reduced mortality, easier to recover from illness, cognitive function, physical and emotional health. The lack of family social support decreases the perceived cause of healing. Method : The design in this research, is descriptive. The population was all General Anxiety Disorders patientsÂ in the Outpatient Installation Kediri Baptist Hospital. In this study sample were taken by purposive sampling techniques, got the number of respondents as much as 54 people. The variable in this study was single variable that was the family social support of patients in the General Anxiety Disorders Outpatient Installation Kediri Baptist Hospital. Conclusion : The results of this research indicated the families social support of General Anxiety Disorders in the Outpatient Installation Kediri Baptist Hospital patients are from 54 people there were 47 people known to have good support (87%).